Elaboração de um instrumento multidimensional para o rastreio de síndrome da fragilidade em idosos atendidos na atenção primária - Lindôso, Zayanna Christine Lopes (2012)
Introduction: the Frailty syndrome (FS) increases the risk of institutionalization, disability and death in the elderly. The concept of fragility evolved into propositions that are no longer limited only to physical and functional aspects. Several authors have studied other dimensions such as psychological and social support structure. However, few studies focused on primary health care.Objective: Develop and validate a multidimensional instrument for frailty screening in elderly patients in primary care.Materials and methods: Cross-sectional, observational, descriptive and analytical, conducted in a random sample of 355 elderly participants Multidimensional Study of the Elderly in Porto Alegre (EMISUS), from 27 different Family Health Strategies of the municipality of Porto Alegre. The elderly were evaluated by an interdisciplinary team. The clinical criteria for determining the phenotype of FS was modified Fried (unintentional weight loss, decreased grip strength, exhaustion and slow walking time - individuals with 0 points were not considered fragile, with 1 point were considered prefrail and those with 2 or more frail).Results: For the development of the instrument, 10 dimensions were initially selected (social (living alone), age (≥80 years old), sensorial (vision, audition and speech), depressed mood, cognition (remembering three words mentioned), medication (5 or more), Daily Life Activities (DLA) / Instrumental activities of daily living (IADL), balance, urinary incontinence and nutrition) categorized as present or not. In the analysis of the degree of concordance between the instrument and the modified Fried phenotype showed low statistical power (degree of concordance = 0.267). It was then performed the multiple logistic regression method Forward Stepwise and five models were generated. The independent predictive variables with greater odds ratio, included in the model 5 where the dimensions were included nutrition (P = 0.019), polypharmacy ( P = 0.005), dependence in DAL / IADL (P = 0.052), urinary incontinence (P = 0.010) and balance (P <0.001). Additionally, it was performed a ROC curve and established a cutoff point of 1/2 to discriminate between individuals of pre-frail/frail not fragile. The instrument sensitivity was 0.759 and specificity was 0.563. The positive predictive value was 0.583 and the negative predictive value was 0.745. The agreement with the IMSIFI Fried phenotype was considered good . By the criteria of Fried, the phenotype was more common non frail (44.5%) following the pre-frail (32.4%). At IMSIFI, most elderly was considered prefrail/ frail (72.9%). It was observed an association between both instruments (Fried and IMSIFI) with functional capacity (DAL / IADL).Conclusion: The instrument developed is objective and of rapid implementation for the context of primary health care. However, longitudinal studies are needed to to compare the IMSIFI with the complete Fried phenotype and other multidimensional instruments, as well as longitudinal studies, are required to prove the role of the IMSIFI in the screening FS